Anacardic acid inhibits RANKL‐induced osteoclastogenesis in vitro and prevents ovariectomy‐induced bone loss in vivo. Issue 8 (3rd May 2019) - Zhao, Kangxian; Jia, Yewei; Peng, Jiaxuan; Pang, Cong; Zhang, Tan; Han, Weiqi; Jiang, Jiawei; Lu, Xuanyuan; Zhu, Jiling; Qian, Yu
ABSTRACT: Postmenopausal osteoporosis is the most common form of primary osteoporosis, and the incidence of the condition is rapidly increasing. In consideration of the limitations of current therapeutic options for the treatment of postmenopausal osteoporosis, there is an urgent need to develop safer alternatives. Anacardic acid, a natural phenolic acid compound extracted from cashew nut shell, possesses potent antitumor and anti‐inflammatory effects and inhibits NF‐κB signaling. However, its effect on osteoclasts remains unknown. This study reports the first evidence for the antiosteoclastogenic and antiresorptive effects of anacardic acid on bone marrow–derived macrophage–derived osteoclasts. Mechanistically, anacardic acid disrupts the phosphorylation of TGF‐β activated kinase 1 and subsequently suppresses multiple receptor activator of NF‐κB ligand–induced signaling cascades, ultimately inhibiting the induction and activation of the crucial osteoclast transcriptional factor nuclear factor of activated T‐cell cytoplasmic 1. Consistent with cellular results in vitro, anacardic acid treatment improves bone density in the murine model of ovariectomy‐induced bone loss. Taken together, our study provides promising evidence for the therapeutic application of anacardic acid as a new potential pharmacological treatment for osteoporosis.—Zhao, K., Jia, Y., Peng, J., Pang, C., Zhang, T., Han, W., Jiang, J., Lu, X., Zhu, J., Qian, Y. Anacardic acid inhibits RANKL‐induced osteoclastogenesis in vitro and prevents ovariectomy‐induced bone loss in vivo . FASEB J. 33, 9100–9115 (2019). www.fasebj.org